TATA KELOLA RUMAH SAKIT UMUM DAERAH SEBELUM DAN SESUDAH BADAN LAYANAN UMUM DAERAH - Febri Yuliani, Tria Anggraini, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Management of Regional General Hospitals Before and After Regional Public Service Bodies. This study aims to determine the management of the Kuantan Singing District Hospital before and after the Regional Public Service Agency (BLUD) was implemented. This study uses a qualitative research method approach. Primary data is obtained directly through interviews from key informants, namely the Teluk Kuantan General Hospital, Health Office, and the community. Secondary data obtained from research documents. The results of the study that the General Management of the Teluk Kuantan Regional Hospital in Kuantan Singingi Regency before using the Regional Public Service Agency experienced many problems in the management of the Regional General Hospital itself so that it interfered with the services, Kuantan Singingi Bay General Hospital Management after using the Agency Regional Public Services since 2017 starting from the Planning, Organizing, Implementing and Supervision phases have been effective. However, there is no direct program that leads to the supervision of the Regional Public Service Agency of the Kuantan Bay General Hospital.